Comparison of bicortical, miniplate and hybrid fixation techniques in mandibular advancement and counterclockwise rotation: A finite element analysis study - VAROL, ALTAN (ELSEVIER, 2021)
Objective: This study aims to evaluate biomechanical stability and stress distribution of five different fixation types with finite element analysis using 10-mm advancement with or without counterclockwise rotation of the mandible. Materials and Methods: After sagittal split osteotomy, 10-mm advancement was performed in the first group and 10-mm advancement and 10-degree counterclockwise rotation were performed in the second group. One miniplate (M-1), two-miniplate (M-2), one miniplate and a bicortical screw (H), L-shaped bicortical screw (B-1), and inverted L-shaped bicortical screw (B-2) systems were placed. Totally, 120 N force was applied to the models at a 45-degree angle from the lower edge of the symphysis. Results: The highest values on fixation were seen with miniplate, while the mean values were obtained with bicortical screw system. The highest values on bone were achieved using bicortical screws. One miniplate (M-1) showed both the highest and mean displacement. The highest values in counterclockwise-rotated models increased in all parameters, compared to non-rotated models. Conclusion: In cases in which passive alignment between segments and adequate bone contact are ensured, inverted L-shaped bicortical screw, two-miniplate, or hybrid systems are recommended. (C) 2021 Elsevier Masson SAS. All rights reserved.
Keywords: Counterclockwise rotation; Finite element analysis; Fixation technique; Mandibular advancement; Occlusal plane alteration; SPLIT-RAMUS OSTEOTOMY; RIGID INTERNAL-FIXATION; SURGERY; STABILITY